PS-097 Complications after vancomycin perfusion by central venous catheter. (24th February 2014) - Soussan Dahan, M; Gautie, L; Rouge, N; Bonnet, E; Giordano, G; Chassery, C; Bicart-See, A
Abstract : Background: Infections and thrombotic events related to Central Venous Catheters (CVC) are iatrogenic complications that may aggravate the initial prognosis. To the best of our knowledge, the risk associated with vancomycin administration by CVC has not been reported in the literature. Purpose: To describe the complications related to vancomycin infusion by CVC experienced in our institute; to identify risk factors and prevent these events. Materials and methods: We performed a retrospective observational study. From April to December 2012, we analysed the data of patients who were given vancomycin by CVC in our institute and who presented either a major complication (thrombotic or infectious) or minor one (blocked catheter, local signs and symptoms such as pain or inflammation). Results: Eight patients matched these criteria. The average age was 61 [27; 80] and sex ratio was 0.3. All patients had at least one risk factor: over 65 years old (n = 4), BMI higher than 25 (n = 4), diabetes and hypertension (n = 3), history of thrombosis (n = 3). All patients were operated on for septic surgery (orthopaedic for n = 7) with intraoperative insertion of double lumen polyurethane CVC. The incision was supraclavian (n = 6) or subclavian (n = 2). Half the patients were transfused. The vancomycin posology ranged from 2 to 4.5 gram per day, corresponding to concentrations from 33 to 75 mg/ml after dilution in sodium chloride 0.9%. Complications occurred by 9.5 days on average [5–20] and resulted in the catheter removal. Three patients developed a minor complication. Five patients presented a major complication: deep vein thrombosis with, for two patients, a catheter-related infection. For one of these two patients, the CVC was infected by Enterobacter cloacae BLSE and Serratia marcescens and, 1.5 months after the operation, his total knee arthroplasty was superinfected by Enterobacter cloacae BLSE with the same profile as the sample from the CVC. Conclusions: These cases underline the potential role of high-dose vancomycin infused by CVC, diluted to concentrations higher than those recommended (10 mg/ml in sodium chloride 0.9% or 40 mg/ml in glucose 5%) in these complications. However, this result must be confirmed by other studies with a larger population. No conflict of interest.